Philosophical foundations of medical law - Phillips, Andelka Matija; Campos, Thana Cristina de; Herring, Jonathan (Oxford : Oxford University Press, 2020)
With advances in personalised medicine, the field of medical law is being challenged and transformed. The nature of the doctor-patient relationship is shifting as patients simultaneously become consumers. The regulation of emerging technologies is being thrown into question, and we face new challenges in the context of global pandemics. This volume identifies significant questions and issues underlying the philosophy of medical law. It brings together leading philosophers, legal theorists, and medical specialists to discuss these questions in two parts. The first part deals with key foundational theories, and the second addresses a variety of topical issues, including euthanasia, abortion, and medical privacy. The wide range of perspectives and topics on offer provide a vital introduction to the philosophical underpinnings of medical law.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 10, 2020).
Keywords: Medical laws and legislation -- Philosophy; Law; Laws of specific jurisdictions & specific areas of law